Numerical investigation of Aloe Vera-mediated green synthesized CuAlO2 as HTL in Pb-free perovskite solar cells - D. K. Sarkar; M. Mottakin; A. K. Mahmud Hasan; Md. Ariful Islam; Md. Mahfuzul Haque; Vidhya Selvanathan; Mohammod Aminuzzaman; Abdulaziz M. Alanazi; Md. Akhtaruzzaman (Journal of Taibah University for Science, 2024)
This study explores green-synthesized delafossite CuAlO2 as a hole transport layer (HTL) in a CH3NH3SnI3-based perovskite solar cells (PSCs) with an FTO/CuAlO2/CH3NH3SnI3/WO3/Au structure. The performances of the cell have been theoretically investigated using SCAPS-1D. Interface defects significantly impact cell efficiency, as defect density increases from 1014 cm−3 to 1020 cm−3 efficiency reducing from 25.3% to 24.45% in the HTL/perovskite junction and from 25.2% to 17.8% in the perovskite/electron transport layer (ETL) interface. PCBM as buffer layer at perovskite/ETL interface compensates for power conversion efficiency (PCE) losses. Optimizing parameters reveals the delafossite CuAlO2-based, lead-free perovskite solar cell achieving peak efficiency at 26.74%, with VOC, JSC, and FF values of 0.99 V, 33.43 mA cm−2, and 81.05%, respectively. This research underscores delafossite CuAlO2 as a promising HTL for eco-friendly, stable CH3NH3SnI3-based perovskite solar cells, emphasizing its potential in enhancing device performance.